Efektivitas dan Kualitas Informasi Konten Youtube Justinus Lhaksana Terhadap Pemenuhan Kebutuhan Informasi Subscribers Pada Review Hasil Kualifikasi Piala Dunia 2026 Fase Grup - Rahmandhito Wiratama, Muhammad; Emilianshah Banowo (Indonesian Journal Publisher, 2025)
A process where the communicator wants to give a message to the communicant and the communicant gives reciprocity to the message given by the communicator is Communication. Justinus Lhaksana's content utilizes the YouTube platform to present relevant information regarding the 2026 World Cup group phase qualifications. The result is to see the effectiveness and quality of YouTube content. The aim of this research is to determine and analyze the effectiveness and quality of the information provided by Justinus Lhaksana towards fulfilling information needs in reviewing the results of the 2026 World Cup qualifying group phase. In the research conducted, researchers used quantitative methods. Quantitative methods are a way to test a particular theory by examining the relationship between variables. Justinus Lhaksana in fulfilling customer information needs in reviewing the results of the 2026 World Cup qualifying group phase. From this research, the results show that there is an influence between effectiveness (X1) and information quality (X2) on fulfilling information needs (Y) of 50.2%, and the rest is influenced by other variables.